RED GINGER RHIZOME EXTRACT GEL IMPROVES COLLAGEN DENSITY POST EXTRACTION OF GUINEA PIG TEETH : GEL EKSTRAK RIMPANG JAHE MERAH MENINGKATKAN KEPADATAN KOLAGEN PASCA EKSTRAKSI GIGI MARMUT - Sulistiawati Putu Dewi; Mochammad Taha Ma’ruf (Interdental Jurnal Kedokteran Gigi (IJKG), 2021)
Introduction: tooth extraction can cause injury involving the bone structure and soft tissue of the oral cavity. Tooth extraction can cause various complications, one of which is bleeding. Red ginger is a type of spice that ismost widely used in various food and beverage recipes. Red ginger is commonly used by the public as a cold, digestive, antipyretic, anti-inflammatory, and analgesic drug. Various studies have shown that ginger has antioxidant properties, flavonoids, and oleoresins found in the rhizome. The purpose of this study was to determine the effect of the concentration of red ginger extract (Zingiber Officinale Varr. Rubrum) on collagen density after extraction of guinea pig teeth (Cavia porcellus). Materials and method: the method of this research is an experimental in vivo laboratory with a post-test-only control group design. The hypothesis test was carried out by the One Way Anova test and was carried out on 24 male guinea pigs. The experimental animals were divided into 4 groups which were distinguished by concentration, 10%, 20%, 30%, and the control group was given 2% CMC-Na gel respectively. Results and discussions: The results showed that red ginger extract gel concentrations of 10%, 20%, and 30% can increase collagen density compared to CMC-Na 2%. Conclusion: the red ginger extract gel with a concentration of 30% was most effective at increasing collagen density compared to concentrations of 10% and 20%.